FACTORS CONTRIBUTING TO THE LIMITED INCLUSION OF NON-WESTERN THINKERS IN THE EVOLUTION OF PUBLIC ADMINISTRATION - Sheikh, Suhail (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
This paper explores the factors that have contributed to the limited inclusion of non-Western thinkers in the evolution of public administration. The field of public administration has been dominated by Western perspectives, which has limited the recognition of non-Western theories and approaches. Historical factors, cultural factors, and institutional factors have all played a role in this limited inclusion. Institutional factors such as educational systems, dominance of Western academic institutions, funding mechanisms, government policies and practices, professional associations, language barriers, publication bias, limited resources, limited access to technology, and lack of representation have all contributed to the limited inclusion of non-Western thinkers in public administration. Addressing these factors will require a greater recognition of the value of non-Western perspectives and a commitment to promoting diversity and inclusion in public administration research and practice.